Effects of Reduced Nitrogen Fertilizer Rates on Its Fate in Maize Fields in Mollisols in Northeast China: A 15N Tracing Study - Ming Liu; Fang Song; Zhihao Yin; Peng Chen; Zhongxue Zhang; Zhijuan Qi; Bai Wang; Ennan Zheng (Agronomy, 2022)
A large amount of nitrogen fertilizer is applied in maize planting in Northeast China, but the recovery rate is low, causing a series of water and soil environmental problems in farmland areas. Thus, based on isotope tracing technology and combining a field plot test with an in situ microzone test, we carried out an experiment under reduced nitrogen fertilizer conditions. Five different nitrogen application levels were set: conventional nitrogen application (N1: 250 kg ha−1), 10%-reduced nitrogen fertilizer (N-10: 225 kg ha−1), 20%-reduced nitrogen fertilizer (N-20: 200 kg ha−1), 30%-reduced nitrogen fertilizer (N-30: 175 kg ha−1), and nitrogen-free (N0: 0 kg ha−1) treatments. Yield, nitrogen accumulation in maize and nitrogen fertilizer fates were studied. The results showed that reducing nitrogen application rates improved the recovery rates of basal fertilizer and topdressing. Specifically, the recovery rate of basal fertilizer was 19.81–26.20%, and the recovery rate of topdressing was 40.24–47.71%. The loss rate of basal fertilizer was 19.96–39.18%, and nitrogen reduction decreased the loss rate of basal fertilizer. The loss rate of topdressing ranged from 36.46 to 41.76%. The residual rates of basal fertilizer and topdressing in the 0–100 cm soil layer were 41.01–53.84% and 12.22–22.30%, respectively. As the nitrogen application rate decreased, corn yield and nitrogen accumulation in maize decreased. Reductions of 20% and 30% in nitrogen fertilizer had a negative influence on plant nitrogen accumulation. This experiment revealed the effect of reducing nitrogen fertilizer application rates on the fate of nitrogen fertilizer, maize yield and nitrogen accumulation in Northeast China. In Northeast China, reducing the nitrogen fertilizer application rate could increase the nitrogen fertilizer recovery rate and reduce nitrogen fertilizer loss amounts and the risk of environmental pollution, but reduce maize yield.